DOI: 10.31274/rtd-180813-7874
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the value of "Source Verification" in Iowa feeder cattle markets

Abstract: CHAPTER 1. INTRODUCTION Background Live-auction sale Source Verification Problem statement Objectives Organization of the study CHAPTER 2. LITERATURE REV1EW Feeder cattle industry Source Verification Factors influencing feeder cattle prices Cattle and lot characteristics Market characteristics Reputation of seller Estimation methods Hedonic pricing models Break-even prices Current trends in feeder cattle marketing CHAPTER3. METHODOLOGY Data Pricing model Determination of optimum price CHAPTER 4. EMPIRICAL RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Increased production and feeding efficiency result from uniform lots of cattle, so some sorting and pooling with the intent to create larger, more uniform sale lots is common. Research has found that buyers pay premiums both for larger and more uniform sale lots (Faminow and Gum;Schroeder et al 1988;Smith et al;Yeboha and Lawrence). For preconditioning programs that include sorting and pooling as part of their protocol, cow-calf producers can expect a price premium for larger, more uniform sale lots of calves.…”
Section: Feeder Cattle Price Differencesmentioning
confidence: 99%
“…Increased production and feeding efficiency result from uniform lots of cattle, so some sorting and pooling with the intent to create larger, more uniform sale lots is common. Research has found that buyers pay premiums both for larger and more uniform sale lots (Faminow and Gum;Schroeder et al 1988;Smith et al;Yeboha and Lawrence). For preconditioning programs that include sorting and pooling as part of their protocol, cow-calf producers can expect a price premium for larger, more uniform sale lots of calves.…”
Section: Feeder Cattle Price Differencesmentioning
confidence: 99%